Peran Sistem Informasi Manajemen dalam Menciptakan Fokus Pelanggan pada Perusahaan - Fatika, Lusiana (Amsir Management Journal, 2024)
A management information system (MIS) is essential for making informed decisions, as it necessitates an understanding of the issues at hand and knowledge of potential solutions. Accurate information leads to more optimal decisions that focus on customer satisfaction. This article employs a qualitative descriptive method and utilizes library research for data collection. The findings indicate that the role of MIS is critical, particularly in contemporary, evolving companies. MIS also contributes to problem-solving and decision-making processes, ultimately serving as a key component in achieving customer satisfaction and focus.